Cote d'Ivoire : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Modifications of Performance Criteria and Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2013)
The Cote d'Ivoire government is working to reform the security apparatus. Containing fiscal risks, strengthening revenue collection, improving public financial management, and creating a business-friendly environment, through regularization of arrears on domestic debt, are the focus of the reform agenda. Sizable debt relief as a result of reaching the HIPC completion has also provided scope for new borrowing to help finance the government's public investment program. Progress on the structural reform agenda and macroeconomic prospects are positive.